2023
DOI: 10.3390/ijms24076732
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Ambroxol Therapy in Type 1 Gaucher Disease Focusing on Patients with Poor Response to Enzyme Replacement Therapy or Substrate Reduction Therapy

Abstract: Ambroxol hydrochloride (ABX), an oral mucolytic drug available over the counter for many years, acts as a pharmacological chaperone for mutant glucocerebrosidase, albeit at higher doses. Proof-of-concept reports have been published over the past decade on all three types of Gaucher disease (GD). Here, we assess the safety and efficacy of 12 months of 600 mg ambroxol per day in three groups of Type 1 GD patients with a suboptimal response to enzyme replacement therapy (ERT) or substrate reduction therapy (SRT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Regarding ambroxol and GD1, although the safety profile seems favorable, clinical responses reported by Zhan et al and Istaiti et al, albeit in very different populations, appear less robust than those reported for ERTs and eliglustat. Perhaps a disconnect exists between the reported good neurological responses and the middling systemic responses, as hinted at in a recent case report in which an infant with type 2 GD who started ambroxol shortly after birth had no neurological progression after 4 years yet had rapid systemic progression requiring institution of ERT.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Regarding ambroxol and GD1, although the safety profile seems favorable, clinical responses reported by Zhan et al and Istaiti et al, albeit in very different populations, appear less robust than those reported for ERTs and eliglustat. Perhaps a disconnect exists between the reported good neurological responses and the middling systemic responses, as hinted at in a recent case report in which an infant with type 2 GD who started ambroxol shortly after birth had no neurological progression after 4 years yet had rapid systemic progression requiring institution of ERT.…”
mentioning
confidence: 81%
“…However, because ambroxol's effects also include inhibition of pH-neutral, nonlysosomal glucocerebrosidase (GBA2), sodium channel blockade, upregulation of intracellular antioxidant and antiapoptotic signaling pathways, and antiinflammatory and immunomodulatory effects, it is uncertain to what extent reported improvements in neurological manifestations in children with GD3 are solely a function of lysosomal GCase activity enhancement. 4 Regarding ambroxol and GD1, although the safety profile seems favorable, clinical responses reported by Zhan et al 1 and Istaiti et al, 7 albeit in very different populations, appear less robust than those reported for ERTs and eliglustat. Perhaps a disconnect exists between the reported good neurological responses and the middling systemic responses, as hinted at in a recent case report 8 in which an infant with type 2 GD who started ambroxol shortly after birth had no neurological progression after 4 years yet had rapid systemic progression requiring institution of ERT.…”
Section: + Related Articlementioning
confidence: 95%
See 1 more Smart Citation
“…These found 36% [39] and 55% [28] of patients reported symptomatic relief. The remaining study reported on changes in laboratory values rather than clinical parameters and did not state whether these were statistically significant.…”
Section: Multiple Laboratory Studies Have Described the Mechanisms By...mentioning
confidence: 94%
“…A single type of GD comprised the entire cohort in seven case series, with the remaining two reporting multiple types (with only one reporting outcomes for these separately [28]). Three case series reported on type 1 GD [28,35,39]. However, only two reported clinical outcomes.…”
Section: Multiple Laboratory Studies Have Described the Mechanisms By...mentioning
confidence: 99%